Rehabilitation of dry agro-pastures through community-based mechanized micro water harvesting and flood-irrigation agriculture to benefit to 1,000 ha/ year in Jordan - CGIAR Research Program on Water, Land and Ecosystems (2020)
Mechanized micro-water harvesting packages developed by ICARDA and the Jordanian National Agricultural Research Center (NARC) are being scaled out in collaboration with local communities, targeting at least 1,000 hectares per year and 20,000 km2 in the long term. The community-based approach effectively rehabilitates degraded dry agro-pastoral watersheds through water harvesting, plantation of native vegetation, and enhanced downstream flood-water agriculture. Community empowerment ensures long-term sustainability of the interventions. The program is expected to equip communities better for drought conditions while improving carbon storage in the uplands and reducing the need for agricultural inputs in the lowlands.